2021
DOI: 10.1101/2021.09.07.459226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifespan analysis of dystrophic mdx fast-twitch muscle morphology and its impact on contractile function

Abstract: Duchenne muscular dystrophy is caused by the absence of the protein dystrophin from skeletal muscle and is characterized by progressive cycles of necrosis/regeneration. Using the dystrophin deficient mdx mouse model we studied the morphological and contractile chronology of dystrophic skeletal muscle pathology in fast twitch EDL muscles from animals 4-22 months of age containing 100% regenerated muscle fibers. Catastrophically, the older age groups lost ~80% of their maximum force after one eccentric contracti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 102 publications
(285 reference statements)
4
5
1
Order By: Relevance
“…Figure 3A shows that there was a graded reduction of force with each EC for both NAC treated and untreated muscles. As has been previously reported mdx muscle were significantly more susceptible to EC induced force loss when Frontiers in Physiology frontiersin.org compared to age matched LC (Kiriaev et al, 2018;Kiriaev et al, 2021a) and this was not altered by treatment with NAC. Figure 3B shows the rate of recovery of force over 60 min, mdx muscles recovered ~20% and this recovery was not different in EDL muscles from NAC treated mdx.…”
Section: Percentage Force Loss Resulting From a Series Of Six Ecs At ...supporting
confidence: 78%
See 3 more Smart Citations
“…Figure 3A shows that there was a graded reduction of force with each EC for both NAC treated and untreated muscles. As has been previously reported mdx muscle were significantly more susceptible to EC induced force loss when Frontiers in Physiology frontiersin.org compared to age matched LC (Kiriaev et al, 2018;Kiriaev et al, 2021a) and this was not altered by treatment with NAC. Figure 3B shows the rate of recovery of force over 60 min, mdx muscles recovered ~20% and this recovery was not different in EDL muscles from NAC treated mdx.…”
Section: Percentage Force Loss Resulting From a Series Of Six Ecs At ...supporting
confidence: 78%
“…The fast twitch EDL muscles of mdx mice have long been known to be more susceptible to damage from EC compared to age match WT controls, as measured by a reduction in Po post EC (Head et al, 1992) and this was confirmed in later studies which utilized LCs for the mdx mice (Kiriaev et al, 2018). In the present study we use a strong eccentric contraction protocol that produced a ~90% Po force loss in mdx which only recovered to ~20% of Po after 60 min demonstrating that it was likely the EC had caused significant membrane damage (Olthoff et al, 2018).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…(2017) in a new cohort of mice aged to 12 months. The 12 month age group was selected because we have previously demonstrated that by this age mdx fast-twitch EDL muscles are irreversibly damaged by a single eccentric contraction, and this irreversible eccentric force deficit is correlated with the number and complexity of branched dystrophic fibres present (Kiriaev et al ., 2018; Kiriaev et al ., 2021b). We found convincing correlative evidence that the age related protective effect conferred by the absence of α-actinin-3 is due to the reduction in the number and complexity of pathologically branched dystrophic fibres.…”
Section: Introductionmentioning
confidence: 99%